An experimental study on intrastromal injection of amphotericin bin fusarium solan/keratitis in rabbits - Che Mahiran, Che Daud (2008)
To compare the effectiveness between intrastromal injection of amphotericin B 0.15% (1.5mg/ml) and intrastromal injection of amphotericin B 0.0005% (5Jlg/ml) and the safety of intrastromal injection Amphotericin B 0.0005% in Fusarium so/ani keratitis in rabbits. Methodology: Fungal keratitis was induced with a standardized inoculum of Fusarium so/ani placed on the debrided cornea into the right eye of 18 New Zealand white rabbits. Rabbits in Group A (n=6) were treated with topical 0.1 5% amphotericin B every hourly for 12 hours daily (control), while rabbits in Group B (n=6) were treated with intrastromal injection 0.15 % (1.5mg/ml) of amphotericin B and Group C rabbits (n=6) were treated with intrastromal injection 0.0005% (5J.Lg/ml) of amphotericin B. The intrastromal injection was given at day 3, 6, 9 and 11. Serial clinical examination was conducted at day 3, 6, 9, 11 and 14 to look at the changes in the size of the epithelial defect, the depth of the ulcer, stromal infiltration, hypopyon and the presence of satellite lesion. The infected eyes were enucleated on the day 14 and sent for histopathology evaluation. Results: The intrastromal injection of amphotericin B 0.0005% injection (group C) was found to be effective compared to intrastromal injection amphotericin B 0.15% (p<O.OO 1) in treating Fusarium keratitis in rabbits. There was statistical significant difference in the size of epithelial defect (p=0.02) and satellite lesion (p=0.02) for the rabbits treated with intrastromal injection of amphotericin B 0.0005% compared to the intrastromal injection of amphotericin B 0.1 5%. Histopathological examination also revealed absence of fungal load, the depth of ulcer limited to anterior two third, moderate inflammatory responses and mild granulation tissue in the group treated with intrastromal injection amphotericin B 0.0005%. These histopathological findings were consistent with serial clinical observation. There was no evidence of corneal decompensation, severe punctate keratopathy and or corneal melting in the group treated with intrastromal injection amphotericin B 0.0005%. Conclusion: Intrastromal injection of amphotericin B 0.0005% (5J.1g/ml) was found to be effective and safe in treating Fusarium so/ani keratitis. Thus, after undergoing clinical trial it can be applied to the patient whose refractory to conventional therapy and can reduce the cost and shorten the hospital stay.